دراسة نقدية في كتاب : السنة الرسولية، والسنة النبوية رؤية جديدة لمحمد شحرور - رشيد، محمود أحمد يعقوب (جامعة آل البيت - عمادة البحث العلمي, 2016)
تهدف هذه الدراسة إلى نقد الأفكار التي طرحها د. محمد شحرور في كتابة (السنة الرسولية، والسنة النبوية رؤية جدية) وتتمثل خطورة هذا الكتاب كونه يطرح مفاهيم جديد للسنة النبوية لهدم المفاهيم الحديثية التي وضعها المحدثون، والتي مرت بمرحلة طويلة من النقد والدراسة والتأصيل حتي استقرت، وشكلت تلك المفاهيم منظومة تحكم عمل الدارسين والباحثين والنقاد في الحديث النبوي وعلومه، لقد وضع د. شحرور مفاهيم جديدة تسيء إلى السنة النبوية، وتهدم حجيتها، ومن أخطر المفاهيم التي طرحها د. شحرور ونقدتها هذه الدراسة: مفهوم في تعريف السنة، ومفهومة للسنة الرسولية، ومفهومه للسنة النبوية، ومفهومه للقصص المحمدي، والاجتهادات النبوية.
This study aims at criticizing ideas put forward by Muhammad Shahrour in his book: (a messenger sunnah, and the Prophetic Sunnah - new vision) The seriousness of this book is in its raising new concepts of the Prophetic Sunnah to demolish the concepts developed by the muhadetheen , which went through a long period of criticism, study and rooting until stabilized, and it formed these concepts system work of scholars and researchers Control and critics in the Hadith and its scicnces, and the development of new concepts detrimental to the Sunnah, and the destruction of authentic, it is the most dangerous concepts put forward by. shahror his criticism to the: concept and the definition of the sunnah, and his concept of apostolic sunnah, and the concept of the Prophetic Sunnah, and the concept of the stories Mohammadi, and prophetic interpretations.
Keywords: أصول الفقه الإسلامي; حجية السنة